Subaltern voices in Sabahattin Ali’s stories - Çetinkaya, Esma Nur (My University, 2016)
Sabahattin Ali is one of the most important writers of 20th century modern Turkish literature. Many protagonists in Sabahattin Ali's works are out of the majority and they are oppressed by the authority. In this thesis my aim is to show that these oppressed, nameless or lower class characters can be assessed as subalterns. It was first Antonio Gramsci who used the terms subaltern and subalternity in Prison Notebooks in 1928. These terms have been adopted and studied elaborately by post- colonial scholars such as Gayatri Chakravorty Spivak, Ranajit Guha and Dipesh Chakrabarty after Gramsci and Subaltern Studies became a school since then. According to this school, it became important to revise the historical and literary texts because by means of these texts we can see the presence of those subjects who are lost or we regard as lost. In fact they continue to live in the texts which we can call as non-state sources. Antonio Gramsci's conceptualization and the researches of pioneer scholars of Subaltern Studies also opened a new pathway for historiography. For example scholars such as Necmi Erdoğan, Mahmut Mutman, Boğaç Ergene, and Umut Yıldırım used the subaltern concept for alternative historiographical understanding in Turkey. With reference to those scholars I aim to show that some stories of Sabahattin Ali can also be assessed within the scope of subalternity. For example it is possible to analyze the clash between the peasants and city people, the oppression of those characters, alienation of some intellectual characters from the majority from the perspective of subalternity. I think that Sabahattin Ali uses the concept of voice both realistically and metaphorically and one of the most significant elements in the works I examined will be the concept of voice in fact the voicelessness. Sabahattin Ali is one of the most important writers of 20th century modern Turkish literature. Many protagonists in Sabahattin Ali's works are out of the majority and they are oppressed by the authority. In this thesis my aim is to show that these oppressed, nameless or lower class characters can be assessed as subalterns. It was first Antonio Gramsci who used the terms subaltern and subalternity in Prison Notebooks in 1928. These terms have been adopted and studied elaborately by post- colonial scholars such as Gayatri Chakravorty Spivak, Ranajit Guha and Dipesh Chakrabarty after Gramsci and Subaltern Studies became a school since then. According to this school, it became important to revise the historical and literary texts because by means of these texts we can see the presence of those subjects who are lost or we regard as lost. In fact they continue to live in the texts which we can call as non-state sources. Antonio Gramsci's conceptualization and the researches of pioneer scholars of Subaltern Studies also opened a new pathway for historiography. For example scholars such as Necmi Erdoğan, Mahmut Mutman, Boğaç Ergene, and Umut Yıldırım used the subaltern concept for alternative historiographical understanding in Turkey. With reference to those scholars I aim to show that some stories of Sabahattin Ali can also be assessed within the scope of subalternity. For example it is possible to analyze the clash between the peasants and city people, the oppression of those characters, alienation of some intellectual characters from the majority from the perspective of subalternity. I think that Sabahattin Ali uses the concept of voice both realistically and metaphorically and one of the most significant elements in the works I examined will be the concept of voice in fact the voicelessness.
Tez (Yüksek Lisans) - Yıldız Teknik Üniversitesi, Sosyal Bilimler Enstitüsü, 2016
Keywords: Sabahattin Ali; Subaltern; Intellectual subaltern; Subalternity; Authority